Politics and religion in Zimbabwe: the deification of Robert G. Mugabe - Chitando, Ezra (Routledge studies on religion in Africa and the diaspora, 2020)
Introduction: Politics and Religion: The Deification of Robert MugabeEzra Chitando1. "Land Comes First Before All Else": Robert G. Mugabe, Land and Salvation for Black AfricansEzra Chitando2. The power of Robert Mugabe's discourses in International RelationsXaman Minillo3. Religio-Political Convergence: A Mugabe-istic tactic to secularize Eccesiastical Authority in Zimbabwe Martin Mujinga4. The Making of a Legend in the Narratives on Robert G. Mugabe's Life and PoliticsMasiiwa Ragies Gunda5. Statecraft: Mugabe and African Traditional Religions Tarisayi Andrea Chimuka6. Was Robert Mugabe the Re-incarnation of Nehanda? An Analysis of Chenjerai Hove's Bones (1989)Kundai Watson Fingson and Tanaka Chidora7. Willing Allies? African Independent Churches and Robert MugabeVengesai Chimininge8. "It shall be well with Zimbabwe": Pentecostalism, Pan Africanism and Discourses on Nation-Building and Restoration in Zimbabwe Kudzai Biri9. "Wolves in sheep clothing"? Robert Mugabe and the media agenda on the prosperity gospelWellington Gadzikwa10. Woman as Scapegoat in the Jezebel and Grace Mugabe NarrativesHonoured Taruona11. Robert Gabriel Mugabe as a Black/African Theologian and Philosopher: A Critical AppreciationRobert Matikiti12. Robert Mugabe's Role as a Man-god in Zimbabwe and the Final JudgementBlessing Nyahuma